2014
DOI: 10.1002/ppul.23039
|View full text |Cite
|
Sign up to set email alerts
|

Lung function by impulse oscillometry at age 5–7 years after bronchiolitis at age 0–6 months

Abstract: Though reduced lung function and increased airway reactivity were rather common, evidence for persistent lung function reduction was rare, less than 1%, at preschool age in children hospitalized for bronchiolitis caused mainly by respiratory syncytial virus at age less than 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(85 citation statements)
references
References 31 publications
6
77
2
Order By: Relevance
“…However, in contrast to the previous studies, a Finnish study indicated a potentially more restrictive pattern of lung function abnormality, documented by significantly decreased FVC values concomitantly with normal FEV 1 values and even elevated FEV 1 /FVC values [64]. Finally, another recent study from Finland observed that less than 1% of 5- to 7-year-old children, hospitalized for bronchiolitis caused mainly by RSV at age <6 months, had persistent lung function reduction [65]. …”
Section: Resultsmentioning
confidence: 99%
“…However, in contrast to the previous studies, a Finnish study indicated a potentially more restrictive pattern of lung function abnormality, documented by significantly decreased FVC values concomitantly with normal FEV 1 values and even elevated FEV 1 /FVC values [64]. Finally, another recent study from Finland observed that less than 1% of 5- to 7-year-old children, hospitalized for bronchiolitis caused mainly by RSV at age <6 months, had persistent lung function reduction [65]. …”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our present study, which did not demonstrate BDR in respiratory resistance, but in respiratory reactance in children with PIBO, assessment of forced expiratory volume in one-second may have limitation for the detection of BDR, especially in small airways. Although there have been studies on followup in children with PIBO using spirometry and children with a history of bronchiolitis in early infancy using IOS (29,30), studies on the change of lung function using IOS during follow-up in children with PIBO are lacking. However, the levels of Xrs5 in children with PIBO did not still reach those in the nonatopic control and asthmatic groups even after the administration of a bronchodilator.…”
Section: Discussionmentioning
confidence: 99%
“…The age criterion for bronchiolitis in these studies was less than 12 months. Our patients were hospitalised at less than six months of age and RSV caused 70% of all the cases in infancy and 60% of those who completed the follow‐up period . Thus, former non‐RSV bronchiolitis patients were more likely to take part in our study than former RSV bronchiolitis patients, and that might have been reflected in our high numbers of allergic rhinitis and atopy.…”
Section: Discussionmentioning
confidence: 99%
“…Complete IOS measurements, at baseline and after the exercise challenge test (ECT), and bronchodilation (BD) tests were available for 103 of these 127 children, as previously published . One child with no history of prolonged rhinitis or asthma refused to undergo the SPT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation